Selection and preparation method of microbial fuel cell catalyst carrier

Analyzing the microcrystalline structure of carbonized materials through Raman spectroscopy solves the problem of single selection index of activated carbon, improves preparation control accuracy and product quality, and provides theoretical support for the promotion of bioelectrocatalytic technology.

CN119334926APending Publication Date: 2025-01-21ANSTEEL BEIJING RES INST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411401178.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the prior art, the selection index of activated carbon of microbial fuel cell catalyst support is single, making it difficult to accurately evaluate its performance, and the diversity and quality requirements of coal species are improved, so more abundant characterization indicators are needed.

Method used

Raman spectroscopy analysis was used to characterize the microcrystalline structure of the carbonized material during the preparation process of activated carbon, and correlated it with the performance indicators of activated carbon to provide evaluation indicators and usage suggestions.

Benefits of technology

It improves the control accuracy of the activated carbon preparation process, reduces production costs, improves product quality, and provides theoretical support for the promotion of bioelectrocatalytic high-efficiency electrode collaborative water treatment technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119334926A_ABST
    Figure CN119334926A_ABST
Patent Text Reader

Abstract

The invention relates to a selection and preparation method of a microbial fuel cell catalyst carrier. The selection method comprises the following steps: 1) pretreating a coal sample; 2) Raman spectrum testing; 3) processing test data and judging the graphitization degree; and 4) judging whether the activated carbon prepared by taking the corresponding coal type of the sample coal as the raw material can be used as the catalyst carrier of the microbial fuel cell. The preparation method comprises the following steps: 1) preparing activated carbon; and 2) treating the catalyst carrier. The microcrystal structure of the carbonized material in the activated carbon preparation process is represented by Raman spectrum analysis and is associated with the performance indexes of the activated carbon, so that evaluation indexes and use suggestions are provided for production and model selection of the activated carbon, the control precision of the activated carbon preparation process is improved, the production cost is reduced, and the product quality is improved; and a theoretical support is provided for popularizing a bioelectrocatalysis efficient electrode synergistic water treatment technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of microbial fuel cells, and in particular to a method for selecting and preparing a catalyst carrier for a microbial fuel cell. Background Art

[0002] MFC (microbial fuel cell) technology is a technology that uses microorganisms as catalysts to convert chemical energy in fuel (organic matter) into electrical energy, and has the dual functions of power generation and waste treatment. Its fuel sources are extensive, especially waste such as organic wastewater, thus bringing new ideas to the treatment of organic wastewater. In recent years, some scholars have applied MFC technology to the treatment of wastewater from multiple industries such as domestic sewage, organic wastewater and food wastewater.

[0003] Compared with conventional fuel cells, MFC technology uses microorganisms instead of expensive chemical catalysts and has the following advantages:

[0004] (1) Directly convert the chemical energy of the substrate into electrical energy, with high energy utilization rate;

[0005] (2) The raw materials are wide-ranging. In theory, any organic matter can serve as a substrate for microorganisms.

[0006] (3) Microbial fuel cells can operate in an environment with normal temperature and pressure, and the operating conditions are mild;

[0007] (4) Environmentally friendly. The substances produced are mainly CO2 and H2O, without any pollutants such as acid, alkali, and heavy metals. There is no need for any post-treatment of the product, which is environmentally friendly and pollution-free, and has good biocompatibility;

[0008] (5) There is no combustion step in the energy conversion process, and the theoretical conversion efficiency is relatively high.

[0009] According to the type of cathode catalyst carrier, MFC cathode catalyst carriers can be divided into graphene, carbon nanotubes, carbon-based materials, activated carbon particles, etc., among which the selection of activated carbon is crucial to the water treatment effect. At present, there are many types of commercial activated carbon available on the market, but the quality is uneven. Common indicators for evaluating the performance of activated carbon, such as iodine value, methylene blue value and caramel decolorization rate, have problems such as large human errors, complex testing process and long testing process. Therefore, there is an urgent need for a method for selecting and preparing activated carbon for microbial fuel cell catalyst carriers that can be fast, accurate and convenient for actual on-site use.

[0010] my country has abundant coal resources. In the past, the raw coal for activated carbon was mainly bituminous coal. After more than 30 years of high-intensity mining, the cost of high-quality bituminous coal has increased significantly. In recent years, the types of coal used as raw materials for activated carbon have gradually increased, the degree of coalification has widened, and the carbonization process has developed from single-type coal to blended coal. The most critical part of the carbonization process is the process control of coal pyrolysis to obtain carbonized precursors, and the coal quality parameters have a significant correlation with the pyrolysis characteristics of coal. The existing characterization indicators for the properties of activated carbon raw coal include ash, volatile matter, elemental composition, calorific value, sulfur content, and bonding index. The above indicators have established the relationship between the properties of coal and the quality of activated carbon from a macroscopic perspective. However, with the continuous improvement of the quality requirements for activated carbon and the continuous increase in coal types, more abundant characterization indicators are urgently needed for the evaluation of activated carbon raw materials. At present, the identification of coal molecular structure and functional groups in coal mainly relies on modern spectral characterization instruments, mainly Fourier transform infrared spectroscopy, Raman spectroscopy and solid nuclear magnetic resonance. These instruments have a certain role in accurately identifying coal structure.

[0011] With the continuous development of microbial fuel cell technology, a technology has emerged that couples biological action and catalytic oxidation to synergistically treat high-concentration organic wastewater. This technology has very strict requirements on the performance of the catalyst, and at the same time puts forward higher requirements on the selection of activated carbon as a catalyst carrier. In the preparation process of activated carbon, the microcrystalline structure of the carbonized material is crucial to the performance of the activated carbon product. The main methods for characterizing the microcrystalline structure of carbonized materials are X-ray diffraction and Raman spectroscopy. Since the carbon-based structure of the carbonized material will have a greater interference with the XRD test results, Raman spectroscopy has gradually become a more mainstream method for detecting the microcrystalline structure of carbonized materials. For example, in the article "Composition and structural evolution of graphene oxide prepared from Shenfu bituminous coal and its coal rock components" (Liu Guoyang et al., "Clean Coal Technology" Issue 02, 2024), the ratio of the D peak and the G peak of the Raman spectrum is used to determine the degree of defects in graphene; in the article "Study on the factors affecting the carbonization of sewage sludge and its adsorption of tetracycline" (Zhou Cuihong et al., "Journal of Beijing Institute of Petrochemical Technology" Issue 31, 2023), the graphitization degree of carbonized sludge is determined by Raman spectroscopy; in the article "The influence of carbonization temperature on the structure of Robinia charcoal" (Kong Fanzhu et al., "Chemical Engineering and Equipment", Issue 07, 2022), the graphitization degree of Robinia charcoal is determined by analyzing the Raman spectrum. However, the current research results are not precise enough in the peak separation method of Raman spectroscopy, which makes the research results prone to deviations. At the same time, the physical properties such as the degree of graphitization cannot be associated with the physical properties of activated carbon, making it difficult to directly use it as a theoretical basis for the production and preparation of activated carbon. Summary of the invention

[0012] The present invention provides a method for selecting and preparing a catalyst carrier for a microbial fuel cell, which is used to solve the problem that the current selection index of activated carbon as a cathode catalyst carrier for bioelectrocatalysis is single and it is difficult to accurately evaluate its performance. Raman spectroscopy analysis is used to characterize the microcrystalline structure of the carbonized material in the activated carbon preparation process, and it is associated with the activated carbon performance index, thereby providing evaluation indexes and usage suggestions for the production and selection of activated carbon, which is beneficial to improving the control accuracy of the activated carbon preparation process, reducing production costs, and improving product quality, and providing theoretical support for promoting bioelectrocatalytic high-efficiency electrode synergistic water treatment technology.

[0013] In order to achieve the above object, the present invention adopts the following technical solutions:

[0014] A method for selecting a catalyst carrier for a microbial fuel cell comprises the following steps:

[0015] 1) Coal sample pretreatment;

[0016] The coal samples are cleaned, crushed, dried to constant weight, and sealed for later use; the coal samples are dried before testing;

[0017] 2) Raman spectroscopy test;

[0018] Before the test, the coal sample was adhered to the surface of the glass slide with double-sided tape; a laser with an output wavelength of 532nm or 633nm was used, the scanning time was set to 0.1-5s, the cumulative number of scans was 10-300 times, and the Raman shift was 800-2000cm -1 ;

[0019] 3) Test data processing and graphitization degree determination;

[0020] The Raman spectrum obtained by the test was subjected to peak fitting using data processing software. The D peak used to determine the degree of graphitization was located at 1300 cm -1 Raman shift, G peak is located at 1590cm -1 Raman shift;

[0021] According to the area obtained in the peak fitting process, the peak area ratio S value is calculated using the formula S = ID / IG, where T D is the peak area of ​​D, I G is the G peak area; the larger the S value, the lower the graphitization degree of the sample coal;

[0022] 4) Determine whether the activated carbon prepared from the corresponding coal type of the sample coal can be used as a catalyst carrier for microbial fuel cells; the judgment criteria are as follows:

[0023] When the S value is ≤2.05, the obtained activated carbon cannot be used as a catalyst support;

[0024] When the S value is ≥2.2, the obtained activated carbon is further tested to determine whether it can be used as a catalyst carrier based on the test results;

[0025] When 2.05<S value<2.2, the prepared activated carbon can be directly used as a catalyst carrier.

[0026] In the step 1), the coal sample is crushed into blocks with a particle size of 0.5 to 2 cm; the coal sample is dried in an electric constant temperature drying oven at 20 to 60° C. under vacuum conditions; the drying is carried out in an electric constant temperature drying oven at 20 to 60° C. under vacuum conditions for 30 to 120 minutes.

[0027] In the step 3), the structure represented by each peak after peak fitting is as follows:

[0028] G L -carbonyl group, C=O;

[0029] G-Graphite E 2g 2 , one quarter of the molecular ring of aromatic hydrocarbons breathes, olefins C=C;

[0030] G R -3-5 membered aromatic ring, amorphous carbon;

[0031] V L -Methyl or methylene, amorphous carbon;

[0032] V R -Methyl, amorphous carbon;

[0033] D-highly ordered D band, CC between aromatic rings and aromatic groups with no less than 6 rings;

[0034] S L - arylalkyl ethers;

[0035] SC 芳烃 -C 烷烃 , aromatic ethers;

[0036] S R -CH structure of aromatic ring;

[0037] R-CC structures of alkanes and cycloalkanes;

[0038] During the peak fitting process, the peak values ​​corresponding to each structure are ensured to float within the set range, where SL and SC 芳烃 -C 烷烃 The peak deviation does not exceed ±15cm -1 .

[0039] The setting intervals are as follows:

[0040] GL : 1700±20cm -1 ;

[0041] G: 1590±20cm -1 ;

[0042] G R :1540±20cm -1 ;

[0043] V L :1465±20cm -1 ;

[0044] V R :1380±20cm -1 ;

[0045] D: 1300±20cm -1 ;

[0046] S L :1230±20cm -1 ;

[0047] SC 芳烃 -C 烷烃 :1180±15cm -1 ;

[0048] S R :1060±15cm -1 ;

[0049] R: 950±20cm -1 .

[0050] In the step 4), further testing includes testing the bulk density ρ and specific surface area of ​​the activated carbon; the determination process is as follows:

[0051] If ρ≤450g / L or ρ≥550g / L, the obtained activated carbon cannot be used as a catalyst carrier;

[0052] If 450≤ρ<500g / L, measure the specific surface area of ​​the coal sample. If the specific surface area is ≥920m 2 / g, the prepared activated carbon can be used as a catalyst carrier, otherwise it cannot be used as a catalyst carrier;

[0053] If the specific surface area is within the range of 500≤ρ≤550g / L, the specific surface area of ​​the coal sample is measured. If the specific surface area is ≥870m 2 / g, the prepared activated carbon can be used as a catalyst carrier, otherwise it cannot be used as a catalyst carrier.

[0054] A method for preparing a catalyst carrier for a microbial fuel cell, the specific preparation process is as follows:

[0055] 1) Preparation of activated carbon;

[0056] Carbonization treatment: The raw coal is carbonized at a temperature of 500-700°C, a carbonization time of 30min-2h, and a heating rate of 1-20°C / min.

[0057] Activation treatment: The raw coal after carbonization is activated by a physical activation method using water vapor or carbon dioxide as an activating agent, with an activation temperature of 800-1000°C and an activation time of 1-4 hours;

[0058] 2) Catalyst carrier treatment;

[0059] Pretreatment of granular activated carbon carrier: The activated carbon particles prepared in process 1) are ultrasonically washed with water until no carbon powder falls off, and the washed activated carbon particles are soaked in industrial alcohol to remove organic matter adhering to the surface, and then drained after being kept for 2 hours, and the residual alcohol is washed with water, and dried at a temperature of 60 to 80° C. for 6 to 24 hours to obtain an AC carrier;

[0060] Metal loading: add 1wt% to 5wt% of metal catalyst to deionized water, then add 1.5 to 2.5wt% of nitrogen source, and stir to obtain a homogeneous solution; load the homogeneous solution onto activated carbon particles by equal volume impregnation method, ultrasonically treat for 20 to 80 minutes, and then dry at 60 to 80°C for 1 to 4 hours;

[0061] The dried activated carbon particles are heated to 350-450° C. at a heating rate of 4-6° C. / min in a muffle furnace and annealed for 1-4 hours to obtain a microbial fuel cell catalyst carrier.

[0062] In process 2), the metal catalyst includes one or both of Co(NO3)2 and Ce(NO3)2.

[0063] Compared with the prior art, the present invention has the following beneficial effects:

[0064] The graphitization degree of carbonized materials is crucial to the formation of mesopores in the subsequent activation stage. Isotropic carbonized materials with low graphitization degree show good pore development in the subsequent activation process, and can produce activated carbon with higher specific surface area and a certain amount of mesopores. The present invention uses Raman spectroscopy to characterize the microcrystalline structure of carbonized materials in the activated carbon preparation process, and correlates it with the performance indicators of activated carbon, thereby providing evaluation indicators and usage suggestions for the production and selection of activated carbon, which is conducive to improving the control accuracy of the activated carbon preparation process, reducing production costs, and improving product quality, and provides theoretical support for the promotion of bio-electrocatalytic high-efficiency electrode synergistic water treatment technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 It is a Raman spectrum diagram obtained by the Raman spectrum test of the present invention. DETAILED DESCRIPTION

[0066] The method for selecting a catalyst carrier for a microbial fuel cell according to the present invention comprises the following steps:

[0067] 1) Coal sample pretreatment;

[0068] The coal samples are cleaned, crushed, dried to constant weight, and sealed for later use; the coal samples are dried before testing;

[0069] 2) Raman spectroscopy test;

[0070] Before the test, the coal sample was adhered to the surface of the glass slide with double-sided tape; a laser with an output wavelength of 532nm or 633nm was used, the scanning time was set to 0.1-5s, the cumulative number of scans was 10-300 times, and the Raman shift was 800-2000cm -1 ;

[0071] 3) Test data processing and graphitization degree determination;

[0072] The Raman spectrum obtained by the test was subjected to peak fitting using data processing software. The D peak used to determine the degree of graphitization was located at 1300 cm -1 Raman shift, G peak is located at 1590cm -1 Raman shift;

[0073] According to the area obtained in the peak fitting process, the peak area ratio S value is calculated using the formula S = ID / IG, where T D is the peak area of ​​D, I G is the G peak area; the larger the S value, the lower the graphitization degree of the sample coal;

[0074] 4) Determine whether the activated carbon prepared from the corresponding coal type of the sample coal can be used as a catalyst carrier for microbial fuel cells; the judgment criteria are as follows:

[0075] When the S value is ≤2.05, the obtained activated carbon cannot be used as a catalyst support;

[0076] When the S value is ≥2.2, the obtained activated carbon is further tested to determine whether it can be used as a catalyst carrier based on the test results;

[0077] When 2.05<S value<2.2, the prepared activated carbon can be directly used as a catalyst carrier.

[0078] In the step 1), the coal sample is crushed into blocks with a particle size of 0.5 to 2 cm; the coal sample is dried in an electric constant temperature drying oven at 20 to 60° C. under vacuum conditions; the drying is carried out in an electric constant temperature drying oven at 20 to 60° C. under vacuum conditions for 30 to 120 minutes.

[0079] In the step 3), the structure represented by each peak after peak fitting is as follows:

[0080] G L -carbonyl group, C=O;

[0081] G-Graphite E 2g 2 , one quarter of the molecular ring of aromatic hydrocarbons breathes, olefins C=C;

[0082] G R -3-5 membered aromatic ring, amorphous carbon;

[0083] V L -Methyl or methylene, amorphous carbon;

[0084] V R -Methyl, amorphous carbon;

[0085] D-highly ordered D band, CC between aromatic rings and aromatic groups with no less than 6 rings;

[0086] S L - arylalkyl ethers;

[0087] SC 芳烃 -C 烷烃 , aromatic ethers;

[0088] S R -CH structure of aromatic ring;

[0089] R-CC structures of alkanes and cycloalkanes;

[0090] During the peak fitting process, the peak values ​​corresponding to each structure are ensured to float within the set range, where SL and SC 芳烃 -C 烷烃 The peak deviation does not exceed ±15cm -1 .

[0091] The setting intervals are as follows:

[0092] G L : 1700±20cm -1 ;

[0093] G: 1590±20cm -1 ;

[0094] G R:1540±20cm -1 ;

[0095] V L :1465±20cm -1 ;

[0096] V R :1380±20cm -1 ;

[0097] D: 1300±20cm -1 ;

[0098] S L :1230±20cm -1 ;

[0099] SC 芳烃 -C 烷烃 :1180±15cm -1 ;

[0100] S R :1060±15cm -1 ;

[0101] R: 950±20cm -1 .

[0102] In the step 4), further testing includes testing the bulk density ρ and specific surface area of ​​the activated carbon; the determination process is as follows:

[0103] If ρ≤450g / L or ρ≥550g / L, the obtained activated carbon cannot be used as a catalyst carrier;

[0104] If 450≤ρ<500g / L, measure the specific surface area of ​​the coal sample. If the specific surface area is ≥920m 2 / g, the prepared activated carbon can be used as a catalyst carrier, otherwise it cannot be used as a catalyst carrier;

[0105] If the specific surface area is within the range of 500≤ρ≤550g / L, the specific surface area of ​​the coal sample is measured. If the specific surface area is ≥870m 2 / g, the prepared activated carbon can be used as a catalyst carrier, otherwise it cannot be used as a catalyst carrier.

[0106] The preparation method of a microbial fuel cell catalyst carrier of the present invention has the following specific preparation process:

[0107] 1) Preparation of activated carbon;

[0108] Carbonization treatment: The raw coal is carbonized at a temperature of 500-700°C, a carbonization time of 30min-2h, and a heating rate of 1-20°C / min.

[0109] Activation treatment: The raw coal after carbonization is activated by a physical activation method using water vapor or carbon dioxide as an activating agent, with an activation temperature of 800-1000°C and an activation time of 1-4 hours;

[0110] 2) Catalyst carrier treatment;

[0111] Pretreatment of granular activated carbon carrier: The activated carbon particles prepared in process 1) are ultrasonically washed with water until no carbon powder falls off, and the washed activated carbon particles are soaked in industrial alcohol to remove organic matter adhering to the surface, and then drained after being kept for 2 hours, and the residual alcohol is washed with water, and dried at a temperature of 60 to 80° C. for 6 to 24 hours to obtain an AC carrier;

[0112] Metal loading: add 1wt% to 5wt% of metal catalyst to deionized water, then add 1.5 to 2.5wt% of nitrogen source, and stir to obtain a homogeneous solution; load the homogeneous solution onto activated carbon particles by equal volume impregnation method, ultrasonically treat for 20 to 80 minutes, and then dry at 60 to 80°C for 1 to 4 hours;

[0113] The dried activated carbon particles are heated to 350-450° C. at a heating rate of 4-6° C. / min in a muffle furnace and annealed for 1-4 hours to obtain a microbial fuel cell catalyst carrier.

[0114] In process 2), the metal catalyst includes one or both of Co(NO3)2 and Ce(NO3)2.

[0115] Renishaw inVia confocal Raman microscope spectrometer (Renishaw inVia Raman spectrometer for short) is the preferred choice for Raman spectroscopy testing. It has two wavelength lasers, 532nm and 633nm, which can meet the testing needs of a variety of materials.

[0116] In order to more intuitively embody the present invention, the embodiments of the present invention are further described in conjunction with examples. The following examples are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any technical solution that can be obviously obtained by a person skilled in the art within the technical scope disclosed in the present invention, including simple changes or equivalent replacements, is within the protection scope of the present invention.

[0117] [Example 1]

[0118] In this embodiment, the selection and preparation process of the microbial fuel cell catalyst carrier is as follows:

[0119] 1. Coal sample pretreatment;

[0120] After the 1# coal sample was collected, it was ultrasonically cleaned with deionized water until there was no floating dust to avoid interference with the subsequent test process. The cleaned 1# coal sample was broken into blocks of about 1 cm, then placed in an electric constant temperature drying oven at 40°C, dried to constant weight under vacuum conditions, and sealed for use. Before testing, the 1# coal sample was vacuum dried at 70°C for 60 minutes.

[0121] 2. Raman spectroscopy test;

[0122] The Renishaw inVia Raman spectrometer was used to characterize the microcrystalline structure of the 1# coal sample. The laser with an output wavelength of 532 nm was selected, the scanning time was set to 0.5 s, the cumulative number of scans was 60, and the Raman shift was 800-2000 cm -1 .

[0125] 3. Test data processing and determination of coal graphitization degree;

[0126] Using data processing software for peak fitting, 10 peaks can be obtained, among which the D peak used to determine the graphitization degree of coal is located at a Raman shift of 1300 cm -1 The G peak is located at the Raman shift of 1590 cm -1 The specific structure and peak position of each peak are shown in the following table:

[0127] structure <![CDATA[G L ]]> G <![CDATA[G R ]]> <![CDATA[V L ]]> <![CDATA[V R ]]> D <![CDATA[S L ]]> <![CDATA[S-C 芳烃 -C 烷烃 ]]> <![CDATA[S R ]]> R <![CDATA[Peak / cm -1 > 1695 1588 1542 1468 1376 1302 1232 1178 1069 942

[0128] According to the peak fitting process, the corresponding area is obtained, and the formula S = I D / I G The calculated peak area ratio S value was 2.17.

[0129] In this embodiment, 2.05<S value<2.2, the activated carbon prepared from the coal type corresponding to the 1# sample coal can be directly used as a carrier of the microbial fuel cell.

[0130] 4. Preparation of activated carbon;

[0131] 1. Carbonization treatment: The raw coal selected and determined in this embodiment is subjected to carbonization treatment, with a carbonization temperature of 650° C., a carbonization time of 1 h, and a heating rate of 10° C. / min.

[0132] 2. Activation treatment: The carbonized raw coal is activated by a physical activation method using carbon dioxide (CO2) as an activating agent, with the activation temperature controlled at 900°C and the activation time at 2.5h.

[0133] 5. Catalyst carrier treatment;

[0134] 1. Pretreatment of granular activated carbon (AC) carrier: A sufficient amount of activated carbon was ultrasonically washed with water until no carbon powder fell off, and the washed activated carbon particles were soaked in industrial alcohol to remove organic matter adhering to the surface, kept for 2 hours and then drained, and the residual alcohol was washed with water, and dried at 70°C for 12 hours to obtain the AC carrier.

[0135] 2. Metal loading: Add 2.5 wt% Co(NO3)2 catalyst (external) to deionized water, then add 2 wt% nitrogen source (external), stir to obtain a homogeneous solution, load the homogeneous solution onto activated carbon particles by equal volume impregnation method, ultrasonically treat for 30 minutes, and then dry in a forced air drying oven at 70°C for 2 hours.

[0136] 3. The dried activated carbon particles were heated to 400°C in a muffle furnace at a heating rate of 5°C / min and annealed for 2 hours to obtain a microbial fuel cell catalyst carrier.

[0137] [Example 2]

[0138] In this embodiment, the selection and preparation process of the microbial fuel cell catalyst carrier is as follows:

[0139] 1. Coal sample pretreatment;

[0140] After the 2# coal sample was collected, it was ultrasonically cleaned with deionized water until there was no floating dust to avoid interference with the subsequent test process. The cleaned 2# coal sample was broken into blocks of about 0.5 cm, then placed in an electric constant temperature drying oven at 45°C, dried to constant weight under vacuum conditions, and sealed for later use. Before testing, the 2# coal sample was vacuum dried at 80°C for 50 minutes.

[0141] 2. Raman spectroscopy test;

[0142] The Renishaw inVia Raman spectrometer was used to characterize the microstructure of the 2# coal sample. The laser with an output wavelength of 532 nm was selected, the scanning time was set to 0.25 s, the cumulative number of scans was 120, and the Raman shift was 800-2000 cm -1 .

[0145] 3. Test data processing and determination of coal graphitization degree;

[0146] Using data processing software for peak fitting, 10 peaks can be obtained, among which the D peak used to determine the graphitization degree of coal is located at a Raman shift of 1300 cm -1 The G peak is located at the Raman shift of 1590 cm -1 The specific structure and peak position of each peak are shown in the following table:

[0147] structure <![CDATA[G L ]]> G <![CDATA[G R ]]> <![CDATA[V L ]]> <![CDATA[V R ]]> D <![CDATA[S L ]]> <![CDATA[S-C 芳烃 -C 烷烃 ]]> <![CDATA[S R ]]> R <![CDATA[Peak / cm -1 > 1704 1592 1538 1463 1368 1303 1228 1192 1057 953

[0148] According to the peak fitting process, the corresponding area is obtained, and the formula S = I D / I G The peak area ratio S value was calculated to be 2.01.

[0149] Since the S value is ≤2.05, the activated carbon prepared in this example cannot be used as a catalyst carrier.

[0150] [Example 3]

[0151] In this embodiment, the selection and preparation process of the microbial fuel cell catalyst carrier is as follows:

[0152] 1. Coal sample pretreatment;

[0153] After the 3# coal sample was collected, it was ultrasonically cleaned with deionized water until there was no floating dust to avoid interference with the subsequent test process. The cleaned 3# coal sample was broken into blocks of about 0.5 cm, then placed in an electric constant temperature drying oven at 40°C, dried to constant weight under vacuum conditions, and sealed for later use. Before testing, the 3# coal sample was vacuum dried at 75°C for 60 minutes.

[0154] 2. Raman spectroscopy test;

[0155] The Renishaw inVia Raman spectrometer was used to characterize the microcrystalline structure of the 3# coal sample. The laser with an output wavelength of 532 nm was selected, the scanning time was set to 1 s, the cumulative number of scans was 60, and the Raman shift was 800-2000 cm -1 .

[0156] 3. Test data processing and determination of coal graphitization degree;

[0157] Using data processing software for peak fitting, 10 peaks can be obtained, among which the D peak used to determine the graphitization degree of coal is located at a Raman shift of 1300 cm -1 The G peak is located at the Raman shift of 1590 cm -1 The specific structure and peak position of each peak are shown in the following table:

[0158] structure <![CDATA[G L ]]> G <![CDATA[G R ]]> <![CDATA[V L ]]> <![CDATA[V R ]]> D <![CDATA[S L ]]> <![CDATA[S-C 芳烃 -C 烷烃 ]]> <![CDATA[S R ]]> R <![CDATA[Peak / cm -1 > 1712 1595 1533 1466 1381 1309 1231 1182 1052 947

[0159] According to the peak fitting process, the corresponding area is obtained, and the formula S = I D / I G The calculated peak area ratio S value was 2.32.

[0160] In this embodiment, the S value is ≥2.2, and the obtained activated carbon needs to be further tested to determine whether it can be used as a catalyst carrier based on the test results.

[0161] 4. Preparation of activated carbon;

[0162] 1. Carbonization treatment: The raw coal selected and determined in this embodiment is subjected to carbonization treatment, with a carbonization temperature of 700° C., a carbonization time of 1 h, and a heating rate of 5° C. / min.

[0163] 2. Activation treatment: The raw coal after carbonization is activated by a physical activation method using carbon dioxide (CO2) as an activating agent, with the activation temperature controlled at 900°C and the activation time at 2h.

[0164] 5. Further screening of activated carbon;

[0165] The bulk density of activated carbon was measured to be 483 g / L. Since it is within the range of 450 ≤ ρ < 500 g / L, the specific surface area of ​​activated carbon needs to be measured. The specific surface area of ​​activated carbon is 967 m 2 / g, and the specific surface area should be ≥870m 2 / g, the activated carbon prepared can be used as a catalyst carrier.

[0166] 6. Catalyst carrier treatment;

[0167] 1. Pretreatment of granular activated carbon (AC) carrier: A sufficient amount of activated carbon was ultrasonically washed with water until no carbon powder fell off, and the washed activated carbon particles were soaked in industrial alcohol to remove organic matter adhering to the surface, kept for 2 hours and then drained, and the residual alcohol was washed with water, and dried at 70°C for 12 hours to obtain the AC carrier.

[0168] 2. Metal loading: Add 2.5 wt% Co(NO3)2 catalyst (external) to deionized water, then add 2 wt% nitrogen source (external), stir to obtain a homogeneous solution, load the homogeneous solution onto activated carbon particles by equal volume impregnation method, ultrasonically treat for 30 minutes, and then dry in a forced air drying oven at 70°C for 2 hours.

[0169] 3. The dried activated carbon particles were heated to 400°C in a muffle furnace at a heating rate of 5°C / min and annealed for 2 hours to obtain a microbial fuel cell catalyst carrier.

[0170] [Example 4]

[0171] In this embodiment, the selection and preparation process of the microbial fuel cell catalyst carrier is as follows:

[0172] 1. Coal sample pretreatment;

[0173] After the 4# coal sample was collected, it was ultrasonically cleaned with deionized water until there was no floating dust to avoid interference with the subsequent test process. The cleaned 4# coal sample was broken into blocks of about 0.5 cm, then placed in an electric constant temperature drying oven at 40°C, dried to constant weight under vacuum conditions, and sealed for later use. Before testing, the 4# coal sample was vacuum dried at 70°C for 60 minutes.

[0174] 2. Raman spectroscopy test;

[0175] The Renishaw inVia Raman spectrometer was used to characterize the microcrystalline structure of the 4# coal sample. The laser with an output wavelength of 532nm was selected, the scanning time was set to 1s, the cumulative number of scans was 60, and the Raman shift was 800-2000cm -1 .

[0176] 3. Test data processing and determination of coal graphitization degree;

[0177] Using data processing software for peak fitting, 10 peaks can be obtained, among which the D peak used to determine the graphitization degree of coal is located at a Raman shift of 1300 cm -1 The G peak is located at the Raman shift of 1590 cm -1 The specific structure and peak position of each peak are shown in the following table:

[0178] structure <![CDATA[G L ]]> G <![CDATA[G R ]]> <![CDATA[V L ]]> <![CDATA[V R ]]> D <![CDATA[S L ]]> <![CDATA[S-C 芳烃 -C 烷烃 ]]> <![CDATA[S R ]]> R <![CDATA[Peak / cm -1 > 1703 1592 1538 1464 1378 1301 1232 1185 1055 944

[0179] According to the peak fitting process, the corresponding area is obtained, and the formula S = I D / I G The calculated peak area ratio S value was 2.42.

[0180] In this embodiment, the S value is ≥2.2, and the obtained activated carbon needs to be further tested to determine whether it can be used as a catalyst carrier based on the test results.

[0181] 4. Preparation of activated carbon;

[0182] 1. Carbonization treatment: The raw coal selected and determined in this embodiment is subjected to carbonization treatment, with a carbonization temperature of 700° C., a carbonization time of 1 h, and a heating rate of 5° C. / min.

[0183] 2. Activation treatment: The raw coal after carbonization is activated by a physical activation method using water vapor (H2O) as an activating agent, with the activation temperature controlled at 900°C and the activation time at 2h.

[0184] 5. Further screening of activated carbon;

[0185] The bulk density of the activated carbon was measured to be 392 g / L. Since ρ≤450 g / L, the prepared activated carbon cannot be used as a catalyst carrier.

[0186] [Example 5]

[0187] In this embodiment, the selection and preparation process of the microbial fuel cell catalyst carrier is as follows:

[0188] 1. Coal sample pretreatment;

[0189] After the 5# coal sample was collected, it was ultrasonically cleaned with deionized water until there was no floating dust to avoid interference with the subsequent test process. The cleaned 5# coal sample was broken into blocks of about 0.5 cm, and then placed in an electric constant temperature drying oven at 40°C, dried to constant weight under vacuum conditions, and sealed for use. Before testing, the 5# coal sample was vacuum dried at 75°C for 60 minutes.

[0190] 2. Raman spectroscopy test;

[0191] The Renishaw inVia Raman spectrometer was used to characterize the microcrystalline structure of the 5# coal sample. The laser with an output wavelength of 532 nm was selected, the scanning time was set to 0.5 s, the cumulative number of scans was 60, and the Raman shift was 800-2000 cm -1 .

[0194] 3. Test data processing and determination of coal graphitization degree;

[0195] Using data processing software for peak fitting, 10 peaks can be obtained, among which the D peak used to determine the graphitization degree of coal is located at a Raman shift of 1300 cm -1 The G peak is located at the Raman shift of 1590 cm -1 The specific structure and peak position of each peak are shown in the following table:

[0196] structure <![CDATA[G L ]]> G <![CDATA[G R ]]> <![CDATA[V L ]]> <![CDATA[V R ]]> D <![CDATA[S L ]]> <![CDATA[S-C 芳烃 -C 烷烃 ]]> <![CDATA[S R ]]> R <![CDATA[Peak / cm -1 > 1710 1591 1537 1463 1379 1301 1232 1182 1061 954

[0197] According to the peak fitting process, the corresponding area is obtained, and the formula S = I D / I G The peak area ratio S value was calculated to be 2.33.

[0198] In this embodiment, the S value is ≥2.2, and the obtained activated carbon needs to be further tested to determine whether it can be used as a catalyst carrier based on the test results.

[0199] 4. Preparation of activated carbon;

[0200] 1. Carbonization treatment: The raw coal selected and determined in this embodiment is subjected to carbonization treatment, with a carbonization temperature of 750° C., a carbonization time of 1 h, and a heating rate of 5° C. / min.

[0201] 2. Activation treatment: The raw coal after carbonization is activated by a physical activation method using water vapor (H2O) as an activating agent, with the activation temperature controlled at 900°C and the activation time at 2h.

[0202] 5. Further screening of activated carbon;

[0203] The bulk density of activated carbon was measured to be 541 g / L. Since it is within the range of 500 ≤ ρ ≤ 550 g / L, the specific surface area of ​​activated carbon needs to be measured. The specific surface area of ​​activated carbon is 903 m 2 / g, and the specific surface area should be ≥870m 2 / g, the activated carbon prepared can be used as a catalyst carrier.

[0204] 6. Catalyst carrier treatment;

[0205] 1. Pretreatment of granular activated carbon (AC) carrier: A sufficient amount of activated carbon was ultrasonically washed with water until no carbon powder fell off, and the washed activated carbon particles were soaked in industrial alcohol to remove organic matter adhering to the surface, kept for 2 hours and then drained, and the residual alcohol was washed with water, and dried at 70°C for 12 hours to obtain the AC carrier.

[0206] 2. Metal loading: Add 2.5 wt% Co(NO3)2 catalyst (external) to deionized water, then add 2 wt% nitrogen source (external), stir to obtain a homogeneous solution, load the homogeneous solution onto activated carbon particles by equal volume impregnation method, ultrasonically treat for 30 minutes, and then dry in a forced air drying oven at 70°C for 2 hours.

[0207] 3. The dried activated carbon particles were heated to 400°C in a muffle furnace at a heating rate of 5°C / min and annealed for 2 hours to obtain a microbial fuel cell catalyst carrier.

[0208] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for selecting a catalyst carrier for a microbial fuel cell, characterized in that: The steps include: 1) Coal sample pretreatment; The coal samples are cleaned, crushed, dried to constant weight, and sealed for later use; the coal samples are dried before testing; 2) Raman spectroscopy test; Before the test, the coal sample was adhered to the surface of the glass slide with double-sided tape; a laser with an output wavelength of 532nm or 633nm was used, the scanning time was set to 0.1-5s, the cumulative number of scans was 10-300 times, and the Raman shift was 800-2000cm -1 ; 3) Test data processing and graphitization degree determination; The Raman spectrum obtained by the test was subjected to peak fitting using data processing software. The D peak used to determine the degree of graphitization was located at 1300 cm -1 Raman shift, G peak is located at 1590cm -1 Raman shift; According to the area obtained in the peak fitting process, the peak area ratio S value is calculated using the formula S = ID / IG, where T D is the peak area of ​​D, I G is the G peak area; The larger the S value, the lower the graphitization degree of the sample coal; 4) Determine whether the activated carbon prepared from the corresponding coal type of the sample coal can be used as a catalyst carrier for microbial fuel cells; the judgment criteria are as follows: When the S value is ≤2.05, the obtained activated carbon cannot be used as a catalyst support; When the S value is ≥2.2, the obtained activated carbon is further tested to determine whether it can be used as a catalyst carrier based on the test results; When 2.05<S value<2.2, the prepared activated carbon can be directly used as a catalyst carrier.

2. The method for selecting a catalyst carrier for a microbial fuel cell according to claim 1, characterized in that: In the step 1), the coal sample is crushed into blocks with a particle size of 0.5 to 2 cm; the coal sample is dried in an electric constant temperature drying oven at 20 to 60° C. under vacuum conditions; the drying is carried out in an electric constant temperature drying oven at 20 to 60° C. under vacuum conditions for 30 to 120 minutes.

3. The method for selecting a catalyst carrier for a microbial fuel cell according to claim 1, characterized in that: In the step 3), the structure represented by each peak after peak fitting is as follows: G L -carbonyl group, C=O; G-Graphite E 2g 2 , one quarter of the molecular ring of aromatic hydrocarbons breathes, olefins C=C; G R -3-5 membered aromatic ring, amorphous carbon; V L -Methyl or methylene, amorphous carbon; V R -Methyl, amorphous carbon; D-highly ordered D band, CC between aromatic rings and aromatic groups with no less than 6 rings; S L - arylalkyl ethers; SC 芳烃 -C 烷烃 , aromatic ethers; S R -CH structure of aromatic ring; R-CC structures of alkanes and cycloalkanes; During the peak fitting process, the peak values ​​corresponding to each structure are ensured to float within the set range, where SL and SC 芳烃 -C 烷烃 The peak deviation does not exceed ±15cm -1 .

4. The method for selecting a catalyst carrier for a microbial fuel cell according to claim 3, characterized in that: The setting intervals are as follows: G L :1700±20cm -1 ; G:1590±20cm -1 ; G R :1540±20cm -1 ; In L :1465±20cm -1 ; In R :1380±20cm -1 ; D:1300±20cm -1 ; S L :1230±20cm -1 ; S-C 芳烃 -C 烷烃 :1180±15cm -1 ; S R :1060±15cm -1 ; R:950±20cm -1 。 5. The method for selecting a catalyst carrier for a microbial fuel cell according to claim 1, characterized in that: In the step 4), further testing includes testing the bulk density ρ and specific surface area of ​​the activated carbon; the determination process is as follows: If ρ≤450g / L or ρ≥550g / L, the obtained activated carbon cannot be used as a catalyst carrier; If 450≤ρ<500g / L, measure the specific surface area of ​​the coal sample. If the specific surface area is ≥920m 2 / g, the prepared activated carbon can be used as a catalyst carrier, otherwise it cannot be used as a catalyst carrier; If the specific surface area is within the range of 500≤ρ≤550g / L, the specific surface area of ​​the coal sample is measured. If the specific surface area is ≥870m 2 / g, the prepared activated carbon can be used as a catalyst carrier, otherwise it cannot be used as a catalyst carrier.

6. A method for preparing a catalyst carrier for a microbial fuel cell, characterized in that: The coal selected by the method for selecting a catalyst carrier for a microbial fuel cell according to any one of claims 1 to 5 is used as raw coal, and the specific preparation process is as follows: 1) Preparation of activated carbon; Carbonization treatment: The raw coal is carbonized at a temperature of 500-700°C, a carbonization time of 30 min-2 h, and a heating rate of 1-20°C / min. Activation treatment: The raw coal after carbonization is activated by a physical activation method using water vapor or carbon dioxide as an activating agent, with an activation temperature of 800-1000°C and an activation time of 1-4 hours; 2) Catalyst carrier treatment; Pretreatment of granular activated carbon carrier: The activated carbon particles prepared in process 1) are ultrasonically washed with water until no carbon powder falls off, and the washed activated carbon particles are soaked in industrial alcohol to remove organic matter adhering to the surface, and then drained after being kept for 2 hours, and the residual alcohol is washed with water, and dried at a temperature of 60 to 80° C. for 6 to 24 hours to obtain an AC carrier; Metal loading: add 1wt% to 5wt% of metal catalyst to deionized water, then add 1.5 to 2.5wt% of nitrogen source, and stir to obtain a homogeneous solution; load the homogeneous solution onto activated carbon particles by equal volume impregnation method, ultrasonically treat for 20 to 80 minutes, and then dry at 60 to 80°C for 1 to 4 hours; The dried activated carbon particles are heated to 350-450° C. at a heating rate of 4-6° C. / min in a muffle furnace and annealed for 1-4 hours to obtain a microbial fuel cell catalyst carrier.

7. The method for preparing a microbial fuel cell catalyst carrier according to claim 6, characterized in that: In process 2), the metal catalyst includes one or both of Co(NO3)2 and Ce(NO3)2.